Borrelia mayonii induces carditis but not arthritis in Lyme-susceptible mice - Cleveland, Dawn W.; Wijetunga, Nivanthi; Casselli, Timothy; Tourand, Yvonne; Pecoraro, Heidi L.; Brissette, Catherine A. (Frontiers in Immunology, 2026)
BackgroundBorrelia mayonii, a Borrelia burgdorferi sensu lato (Bbsl) genospecies, is a cause of Lyme disease in the upper midwestern United States. B. mayonii infection can present with some atypical clinical manifestations, including unusually high spirochetemia. Previous studies have demonstrated the infectivity of B. mayonii in laboratory mice and found evidence of widespread dissemination to internal tissues, however, did not report evidence of high spirochetemia. In the current study, we sought to directly compare spirochetemia as well as typical Lyme disease pathology including arthritis and carditis in Lyme disease-susceptible mice infected with either B. mayonii or B. burgdorferi. MethodsImmunocompetent (C3HeB/FeJ) and immunodeficient (SCID) mice were infected with B. burgdorferi or B. mayonii. Spirochetemia was measured in blood by qPCR, and pathology of hearts and joints examined.ResultsConsistent with previous reports, we found that B. mayonii spirochetemia observed in human patients is not recapitulated in C3H mice and did not reach higher detectable levels compared to B. burgdorferi. Interestingly, tibiotarsal joint swelling and histopathology were restricted to B. burgdorferi-infected mice and were not detected in any B. mayonii-infected mice up to four weeks post-inoculation. Carditis was routinely detectable in both B. mayonii and B. burgdorferi-infected mice, although differences in kinetics and severity were observed. ConclusionTaken together, this study characterizes similarities and differences between B. burgdorferi and B. mayonii in a laboratory model of Lyme disease. These findings add to the immunopathologic landscape caused by distinct genospecies in the Bbsl complex, which could shed light on the distinct host-pathogen interactions important for specific Lyme disease manifestations.